2016
DOI: 10.11143/55485
|View full text |Cite
|
Sign up to set email alerts
|

Participation of second home owners and permanent residents in local decision making: the case of a rural village in Finland

Abstract: (2016). Participation of second home owners and permanent residents in local decision making: the case of a rural village in Finland. Fennia 194: 2, 152-167. ISSN 1798-5617. In Finland, there are almost 500,000 second homes and in some areas the number of second home owners exceeds that of permanent residents. Currently, second home owners are also spending more time in their second homes. If second home owners are not permanent residents, administration may exclude them from local institutions, and treat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 39 publications
(50 reference statements)
1
11
0
Order By: Relevance
“…What deviates Nordic rural areas from most rural areas in the World is the widespread seasonal residence in these areas. It is very common in the Nordic countries to own a cottage or a "second home" located in a rural area [45][46][47]. It has been estimated that nearly half of the Nordic population have access to a second home, and the number of second homes in the Nordics has increased in the recent years [40].…”
Section: Case Nordic Rural Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…What deviates Nordic rural areas from most rural areas in the World is the widespread seasonal residence in these areas. It is very common in the Nordic countries to own a cottage or a "second home" located in a rural area [45][46][47]. It has been estimated that nearly half of the Nordic population have access to a second home, and the number of second homes in the Nordics has increased in the recent years [40].…”
Section: Case Nordic Rural Areasmentioning
confidence: 99%
“…It has been estimated that nearly half of the Nordic population have access to a second home, and the number of second homes in the Nordics has increased in the recent years [40]. Recent trend has been that people spend even more time in their second homes, and year-round usage is increasing [47,48]. On average, people spend multiple months in their second homes every year [48].…”
Section: Case Nordic Rural Areasmentioning
confidence: 99%
“…Spatial planners in municipalities and regions often fear even a marginal decline in population because of a corresponding reduction in the demand for services (Ellingsen, 2016;Kietäväinen et al, 2016). To analyse such a situation correctly, it is important to include second home users (i.e.…”
Section: Spatial Planning For Second Homesmentioning
confidence: 99%
“…They found that municipal actors seem to evaluate the positive impact of second homeowners on infrastructure and services higher than the permanent residents. Kietäväinen et al, point out, however, that the municipal administration may exclude them from local institutions, and treat them as only partial members of the community [36]. The participation of second homeowners in local activities and development projects may bring benefits to the municipality.…”
Section: Introductionmentioning
confidence: 99%